Symphony Lake Dataset. (September 2017) - Griffith, Shane; Chahine, Georges; Pradalier, Cédric
This paper describes Symphony Lake Dataset, 121 visual surveys of an approximately 1.3 km lake shore in Metz, France. Different from roadway datasets, it adds breadth to the data space at a time when larger and more diverse datasets are desired. Over five million images from an unmanned surface vehicle captured the natural environment as it evolved over three years. Variation in appearance across weeks, seasons, and years is significant. Success on Symphony Lake Dataset could demonstrate advancements in perception, simultaneous localization and mapping, and environment monitoring.